Paraneoplastic Cushing's syndrome as an adverse prognostic factor in patients who die early with small cell lung cancer - Dimopoulos, M.A.; Fernandez, J.F.; Samaan, N.A.; Holoye, P.Y.; Vassilopoulou‐Sellin, R. (Cancer, 1992)
The potential role of paraneoplastic Cushing's syndrome (CS) was assessed on the clinical course of patients with small cell lung cancer. A retrospective comparison was done of complication and survival rates according to the presence or absence of CS in patients with small cell lung cancer who died within 90 days of initial administration of chemotherapy. The setting was a comprehensive cancer center. Eleven patients with clinical and/or biochemical features of CS were identified from among 90 patients who presented between 1979 and 1989 with previously untreated small cell lung cancer. The group with CS and the control patients were compared in terms of clinicopathologic prognostic factors, treatment, and outcome. Patients with CS were comparable to the control patients in all prognostic factors, including tumor stage and cancer treatment. Eight‐two percent of patients with CS (nine of 11) died within 14 days of initiation of chemotherapy compared with 25% of the control patients (19 of 77). The median survival from initiation of chemotherapy was 12 days for the 11 patients with CS and 27 days for the 77 control patients. In 45% of the patients with CS (five of 11), death was attributed to opportunistic fungal or protozoal infection compared with 8% of control patients (six of 77). paraneoplastic CS is a previously unrecognized adverse prognostic factor for patients with small cell lung cancer. Those with both small cell lung cancer and CS have severe opportunistic infections soon after the initiation of chemotherapy, leading to clinical deterioration and death before antineoplastic benefit from chemotherapy can be achieved. Biochemical control of CS for at least 1 to 2 weeks before initiation of chemotherapy may ameliorate the poor prognosis. Copyright © 1992 American Cancer Society